Exploring The Use of Board Games in Teaching Prepositions In Phrasal Verbs To University Learners: A Study of BOP - Nargiza Nuratdinova (Indonesian Journal Publisher, 2026)
The process of engaging students in language learning can be approached through various methods, including the use of games and play. Incorporating games to teach languages in educational settings is not a new concept, but many educators remain hesitant to embrace games as a primary teaching tool. Board games, when aligned with curriculum standards and targeted learning objectives, can prove to be both effective and engaging. This study explores the use of BOP (Board games for Organizing Preposition practice) , a formative assessment tool designed as a board game, as an innovative approach to teaching prepositions — specifically on, at, and in — in phrasal verbs to EFL (English as a Foreign Language) and ESP (English for Specific Purposes) students. The study involved 62 voluntary participants from University of Innovation Technologies and Karakalpak State University who completed both a pre-test and post-test to assess their progress in acquiring these prepositions. Additionally, a survey was administered to gauge the students' attitudes and perceptions regarding the use of board games in language learning. The results indicate that the game-based approach was effective in helping learners improve their understanding of phrasal verbs, with most students reporting increased engagement and retention